Bioatividade do solo sob plantio direto com sucessão e rotação de culturas - Barbieri, Mirian (2017)
The adoption of conservation practices can affect the physical, chemical and biological properties of the soil, resulting changes in the composition and activity of the microbial community. The aims of this research was to obtain information about the soil quality, diversity and biological activity, submitted to two types of soil management (scarified (PDE) and no-scarified tillage (PDNE)) and three types of cover management (Succession: soybean-wheat, Rotation I: Soybean-turnip+wheat/soybean-oats+vetch and Rotation II: soybean-oats+vetch+turnip/corn-crotalaria junceawheat/ soybeans).Analyzes of carbon and nitrogen from microbial biomass, soil enzymatic activity (urease, acid phosphatase and FDA), basal respiration rate and genetic diversity analysis were performed using the RAPD technique. Carbon and nitrogen from soil microbial biomass were higher in all treatments under no-scarified no-tillage in both collection periods. The same pattern can be observed for urease enzyme activity, which presented higher values in no-scarified no-tillage soil. All enzymes showed an increase in their activity in the summer period, which shows that they are influenced by temperature and soil moisture. For the basal respiration rate, in the winter period higher values were obtained when compared to the summer period. In addition, in the winter, the highest rate of accumulated CO2 release was observed in noscarified no-tillage, and the opposite was observed for the summer period, where the highest rate was obtained in scarified tillage. The RAPD technique was efficient in detecting the genetic variability among the treatments, grouping them into four groups and generated a profile of genetic markers that can be used in later works to evaluate the genetic diversity in agricultural soils. Based on these results, we concluded that noscarified no-tillage associated with good soil conservation practices, such as permanent coverage through plant residues, contribute to an increase in the values of microbial biomass, respiration rate and enzymatic activity of the soil. RAPD technique associated with other bioindicators become important tools for the monitoring and evaluation of soil quality, activity and biological diversity.